Dysexecutive symptoms and carer strain following acquired brain injury: changes measured before and after holistic neuropsychological rehabilitation - Goodwin, Rachel A.; Lincoln, Nadina; Bateman, Andrew; Parente, Rick (IOS Press, 2016)
BACKGROUND: Following acquired brain injury (ABI), deficits in executive functioning (EF) are common. As a result many brain-injured patients encounter problems in every-day functioning, and their families experience significant strain. Previous research has documented the benefits of cognitive rehabilitation for executive dysfunction, and rehabilitation programmes designed to ameliorate functional problems associated with ABI. OBJECTIVES: This study primarily aims to evaluate whether a neuropsychological rehabilitation programme reduces reported symptoms of everyday dysexecutive behaviour and carer strain. METHODS: In this study 66 ABI outpatients attended comprehensive holistic neuropsychological rehabilitation programme. A repeated-measures design was employed to determine the effect of rehabilitation on EF and carer strain, as part of a service evaluation. Outcome measures comprised the dysexecutive questionnaire (DEX/DEX-I) and carer strain index (CSI), applied pre- and post-rehabilitation. RESULTS: Results indicate rehabilitation benefited clients and carers in 5 of 6 DEX/DEX-I subscales, and 2 of 3 CSI subscales, (p<.05). An effect of aetiology on rehabilitation was found on the metacognitive scale of the DEX-I. CONCLUSIONS: Therefore, this study supports a comprehensive holistic neuropsychological rehabilitation programme as effective in reducing reported symptoms of dysexecutive behaviour and carer strain following ABI.